2019
DOI: 10.1161/jaha.119.013092
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adverse Pregnancy Outcomes With Hypertension 2 to 7 Years Postpartum

Abstract: BackgroundIdentifying pregnancy‐associated risk factors before the development of major cardiovascular disease events could provide opportunities for prevention. The objective of this study was to determine the association between outcomes in first pregnancies and subsequent cardiovascular health.Methods and ResultsThe Nulliparous Pregnancy Outcomes Study Monitoring Mothers‐to‐be Heart Health Study is a prospective observational cohort that followed 4484 women 2 to 7 years (mean 3.2 years) after their first pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
100
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 38 publications
2
100
2
Order By: Relevance
“…The Nurses’ Health Study II demonstrated that women who reported a first pregnancy affected by HDP presented higher rates of hypertension (hazard ratio [HR] 2.8; 95% CI 2.6–3.0), type 2 diabetes mellitus (HR 1.7; 95% CI 1.4–1.9) and hypercholesterolaemia (HR 1.4; 95% CI 1.3–1.5) within 5 years postpartum 37 . A recent prospective observational cohort that followed 4484 women for a mean of 3.2 years after their first pregnancy showed that women with any hypertensive disorder of pregnancy had a higher adjusted risk of hypertension at follow up compared with controls (relative risk [RR] 2.7; 95% CI 2.0–3.6) 38 . Moreover, a register‐based study showed that women with HDP had twice the risk of cardiovascular readmissions (acute myocardial infarction, stroke or heart failure) within 3 years compared with women with normal pregnancies 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The Nurses’ Health Study II demonstrated that women who reported a first pregnancy affected by HDP presented higher rates of hypertension (hazard ratio [HR] 2.8; 95% CI 2.6–3.0), type 2 diabetes mellitus (HR 1.7; 95% CI 1.4–1.9) and hypercholesterolaemia (HR 1.4; 95% CI 1.3–1.5) within 5 years postpartum 37 . A recent prospective observational cohort that followed 4484 women for a mean of 3.2 years after their first pregnancy showed that women with any hypertensive disorder of pregnancy had a higher adjusted risk of hypertension at follow up compared with controls (relative risk [RR] 2.7; 95% CI 2.0–3.6) 38 . Moreover, a register‐based study showed that women with HDP had twice the risk of cardiovascular readmissions (acute myocardial infarction, stroke or heart failure) within 3 years compared with women with normal pregnancies 39 .…”
Section: Discussionmentioning
confidence: 99%
“…In that study, authors reported that women with any hypertensive disorder in pregnancy were more than two times as likely to have hypertension at follow-up (RR 2.7, 95% CI 2.0-3.6). 43 Others found significant increases in high BP as soon as two years postpartum in women with hypertensive disorders of pregnancy, though that sample consisted of primarily white women (from the United Kingdom) as well. 44 Another study reported a significant increase in hypertension risk 12 months postpartum for obese women with preeclampsia (OR 2.35, 95% CI 1.63-3.41).…”
Section: Discussionmentioning
confidence: 95%
“…Most studies 42 looked at cardiovascular outcomes such as heart disease, myocardial infarction, or death, and not a more short-term outcome such as hypertension. Haas et al 43 reported findings of a prospective cohort study of 4484 women followed for 2-7 years after their first pregnancy. Women in this study were recruited from eight centers across the United States and were primarily white (62.1%), and few were African American (13.8%).…”
Section: Discussionmentioning
confidence: 99%
“…have not yet been adequately studied or implemented, to our knowledge. [24][25][26][27] Prior studies have…”
Section: Discussionmentioning
confidence: 99%